Implementasi Media Proyeksi Dalam Learning Qur’an Hadits (LQH) - Doni Saputra (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Projection media is a media that can be used with the help of a projector. This media is a visual medium. It is said to be a viual media because it can visualize an object with its real form. This media is very helpful in providing a learning material that will be conveyed to students. With this projection media, it is hoped that students will find it easier to understand the material presented by the teacher. This disampin also helps teachers to explore their potential to be more creative and innovative in designing instructional media. From research at MTs Taufiqiyatul Asna Buka'an Keling Kepung Kediri Regency, it is applied quite well, and also maximally in the use of existing media such as blackboard media, LKS books, textbooks, props, projector media, computer labs and LCDs that are already available . The subject of Al Qur'an Hadith has a very broad subject matter and material so that learning media is needed in the teaching and learning process so that students do not get bored and tired of listening to teacher explanations with the lecture method without the help of learning / learning media. Al Qur'an Hadith is a field of study that uses a lot of learning media. Whether the available media is complete or not can affect the teaching and learning process, it can even become an obstacle in achieving learning / learning objectives. While the inhibiting factor is that teachers who are old cannot operate existing media except books and blackboards, and students also lack mastery in technology and information sciences.